The response of Abies hickelii to environmental factors in southern Mexico - Gutiérrez, Erick; Trejo, Irma (Instituto de Ecología, A.C., 2023)
Environmental conditions influence several ecological and phenological processes of plant species, such as dispersal, seed bank in the soil, and germination. The objective of the present study was to analyze the relationship between the abundance of adult individuals and seedlings, seed rainfall, germination rate, and survival of Abies hickelii regarding environmental conditions in the Sierra Norte Oaxaca, Mexico. We conducted vegetation sampling, placed traps for seed rain, collected seed banks in the soil, and quantified germination and survival. At each site, we measured environmental conditions (climatic, edaphic, topographic, and light). It was recorded that at the highest altitude site (3150 m), A. hickelii had a higher density of adults and seedlings and a higher percentage of germination compared to the lower altitude sites. The abundance of adult individuals and seedlings of A. hickelii is related to canopy openness and maximum rainfall intensity. Seed production is related to total annual precipitation, while germination and survival were not associated with any of the environmental variables analyzed. This study considered different aspects of the A. hickelii life cycle and its relationship with the environmental conditions where it was established, which allowed us to determine the most significant environmental variables in each growth stage. The results represent relevant information for endemic and endangered species.